A Novel Approach to Minimising Acute Equine Endometritis That May Help to Prevent the Development of the Chronic State - Morrell, J. M.; Rocha, A. (Frontiers in Veterinary Science, 2022)
One of the most commonly encountered challenges in equine breeding is endometritis, which can be difficult to resolve and causes considerable economic losses to the industry. It is a multifactorial condition, developing as an exaggerated form of the normal physiological response to breeding. Seminal plasma proteins, spermatozoa, bacteria and debris initiate an inflammatory response; the resulting fluid and neutrophils are then cleared from the uterus along with the debris. However, in some mares, the response is prolonged or exaggerated, with much fluid formation and neutrophil infiltration leading to acute endometritis. A bacterial cause has been implicated, although in some cases no pathogenic organisms can be isolated on culture. It has been postulated that any one of a variety of bacteria could be involved, or dysbiosis of the uterine microbiome could be responsible. Repeated episodes of acute endometritis may lead to the pathology associated with chronic endometritis, with mucociliary dysfunction, vascular degeneration and plasma cell infiltration. This review examines the information that is currently available about equine endometritis, particularly about the role of the inseminate in the uterus, and its current treatment. There are some promising lines of research into treatment or prevention that we hypothesise may help to resolve the issue.